Determination severity of pneumonia, responses of heat shock protein 90 (HSP 90) and cortisol concentrations in vaccinated and non-vaccinated pneumonic and non-pneumonic goats - Ahmad Tarmizi Tan, Ahmad Hafizin (2018)
Pneumonic pasteurellosis is a common respiratory disease encountered in small ruminants, either in goats or sheep and the common causative agents are Mannheimiahaemolytica and Pasteurella multocida. Vaccination program is seen to be the most cost-effective way to control the disease. Heat shock protein 90 is a stress protein that involves in many functions including protection of cells from stressors, therefore increase expression is expected when the animal is exposed to stress stimuli. Cortisol on the other hand, is a glucocorticoid that also response towards stress stimuli and therefore increase level is expected to see in stressful conditions. There is paucity of information on the severity of pneumonia and responses of heat shock protein 90 (HSP90) and cortisol concentrations in vaccinated and non-vaccinated pneumonic goats. Therefore, this study was designed where total of 76 goats were selected in this study from selected four small ruminant farms. The animals were grouped into three groups namely normal vaccinated and non-vaccinated group, vaccinated pneumonic group and non-vaccinated pneumonic group based on clinical examination. Severity of pneumonia was determined based on scoring of the auscultation and the severity was classified as mild, moderate and severe. Blood samples were collected from these goats and the samples were subjected for heat shock protein 90 (HSP90) and serum cortisol analyses using ELISA technique. The result of this study showed that the non-vaccinated pneumonic goats had higher auscultation score and were classified as moderate to severe clinical signs of pneumonia. The vaccinated pneumonic goats revealed mild pneumonia score. Mean concentration of HSP 90 for normal vaccinated and non-vaccinated group and vaccinated pneumonic group were 32.9pg/ml±4.21 and 33.78pg/ml±5.71 respectively and approximately 1.6 time increased in the concentration observed in non-vaccinated pneumonic group (54.76pg/ml±13.6). For the mean cortisol concentration were 17.74pg/ml±4.43, 22.98pg/ml±4.71 in normal vaccinated and non-vaccinated group and vaccinated pneumonic group respectively and only 19.67pg/ml±3.37 in non-vaccinated pneumonic group.Statistical analysis of HSP 90 and cortisol concentration showed there was no significant difference between three groups. In conclusion, the vaccinated group showed mild host cell responses compared to non-vaccinated group in pneumonic goats.